Potencial biotecnológico dos endófitos associados à pimenta murupi (Capsicum chinense Jacq.) - Nogueira, Janaina da Costa (2014)
Endophytic microorganisms inhabit plant tissues asymptomatically and establish a mutualistic relationship with their hosts. This microbial group is recognized as a source of valuable secondary metabolites with different biological activities for medicine, agriculture, biotechnology and industry. This work was based on the potential of these endophytes and proposes the characterization of those murupi pepper fruits (Capsicum chinense) associated microorganisms, and the evaluation of their ability to produce metabolites with antimicrobial activity. The total number of endophytes obtained from the murupi pepper fruit and seeds was 446 (133 filamentous fungi and 313 bacteria), with 55.75% of isolation frequency. Bacteria were more frequent than fungi, especially in seeds. About 70% of the fungal isolates (comprising 74 morphological groups) could not be identified because they do not produce reproductive structures in culture medium under the established work conditions. For three other groups, it was possible to analyze the macro and micromorphological characteristics of colonies and determine three genera. Fusarium genus was predominant among murupi associated endophytes, presenting cottonous white to pink mycelium and peculiar micromorphological characteristics. Endophytic bacteria were grouped into six morphotypes, based on macroscopic characteristics. For performing antibiosis assay, 77 fungi and 6 bacteria were selected. Just one fungal endophyte showed inhibition zone against methicillin-resistant Staphylococcus aureus (MRSA) and have their DNA submitted to the amplification of the ITS1-5.8S-ITS2 rDNA region, resulting in a band with approximately 600 bp. According to the Blastn performed alignment with NCBI genomic bank sequences, the major identity level (92%) were established with Nemania sp., but this level is considered low and can not be used to infer about some identification. Keywords: Capsicum chinense, endophytic microorganisms, antimicrobial compound.